2020
DOI: 10.1177/0266666920907118
|View full text |Cite
|
Sign up to set email alerts
|

Data challenges for public libraries: African perspectives and the social context of knowledge

Abstract: This article sheds light on the collection and use of data by libraries in sixteen countries across Africa. It highlights the challenges that librarians and library organizations face in gathering, analyzing, and presenting data of various types for self-advocacy. In this study, qualitative data from a meeting of library representatives was analyzed to identify main challenges including: data integrity in terms of completeness, accuracy, credibility, and relevancy; infrastructure; capacity; local investment in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
(28 reference statements)
2
9
0
Order By: Relevance
“…VGI projects need to consider how local cultural understandings of payment/volunteering, data, and privacy intersect with motivations to engage in crowdsourcing, and either adapt their project (e.g., provide payment) or work to change that particular culture (e.g., develop nonpayment based motivation strategies grounded in the local culture). Other aspects of our project have begun to explore how cultural understandings of knowledge production impact local data culture (Lynch et al 2020), but much more research is needed in this area.…”
Section: Librarian Motivationmentioning
confidence: 99%
“…VGI projects need to consider how local cultural understandings of payment/volunteering, data, and privacy intersect with motivations to engage in crowdsourcing, and either adapt their project (e.g., provide payment) or work to change that particular culture (e.g., develop nonpayment based motivation strategies grounded in the local culture). Other aspects of our project have begun to explore how cultural understandings of knowledge production impact local data culture (Lynch et al 2020), but much more research is needed in this area.…”
Section: Librarian Motivationmentioning
confidence: 99%
“…Further, crowdsourced maps can be utilized as political advocacy tools by making small-scale efforts more visible to larger funding or political bodies in the Global South (Young, 2017;Young and Gilmore, 2017). Our work operates on similar hopes of connecting communities with the resources they need for institutional survival through elevating their visibility, as evidence shows that many libraries in Africa do not collect comprehensive data about themselves, which creates challenges in terms of local and international recognition (Lor, 2016;Lynch et al, 2020).…”
Section: Literature Review: Crowdsourcing and Mapping In Librariesmentioning
confidence: 99%
“…This is symptomatic of an even greater problem that faces library systems in the Global South and Africa in particular. In many countries, there is a lack of data culture or systematic method of collecting data about library reach or impact (Lynch et al, 2020;Moahi, 2019). In some cases, the national library or related authorizing institution of a country does not even know how many libraries they have or where they are located.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence shows that African libraries face unique challenges in collecting and utilizing data for self-advocacy. A recent study indicated that library representatives from 16 African countries note challenges concerning data integrity in terms of completeness, accuracy, credibility, and relevancy; infrastructure; capacity; local investment in libraries; time; and participation of data collectors and respondents (Lynch et al, 2020a). Simply conducting a survey of library users requires more time and effort in order to build a relationship of trust with communities who have long been "socially excluded" from library spaces (Kabamba, 2008, p. 156).…”
Section: African Libraries In Developmentmentioning
confidence: 99%
“…While libraries across the continent have affirmed the importance of this visibility, few studies have followed up to determine whether efforts have been successful at achieving it. Given the challenges that African libraries face in collecting and using data effectively (Lynch et al 2020a;Moahi, 2019), the sector needs a more focused strategy that can speak to existing perceptions and understand which types of data would be most effective in shifting the narrative. This research thus illuminates the perception gap that exists between CONTACT Renee Lynch lynchren@uw.edu Technology and Social Change (TASCHA), University of Washington, Seattle, WA, USA.…”
Section: Introductionmentioning
confidence: 99%